The effect of two closely inserted transcription consensus sequences on coronavirus transcription. - Joo, M (1995)
Insertion of an intergenic region from the murine coronavirus mouse hepatitis virus into a mouse hepatitis virus defective interfering (DI) RNA led to transcription of subgenomic DI RNA in helper virus-infected cells. Using this system, we studied how two intergenic regions in close proximity affected subgenomic RNA synthesis. When two intergenic regions were separated by more than 100 nucleotides, slightly less of the larger subgenomic DI RNA (synthesized from the upstream intergenic region) was made; this difference was significant when the intergenic region separation was less than about 35 nucleotides. Deletion of sequences flanking the two intergenic regions inserted in close proximity did not affect transcription. No significant change in the ratio of the two subgenomic DI RNAs was observed when the sequence between the two intergenic regions was altered. Removal of the downstream intergenic region restored transcription of the larger subgenomic DI RNA. The UCUAAAC consensus sequence was needed for efficient suppression of the larger subgenomic DI RNA synthesis. These results demonstrated that the downstream intergenic sequence was suppressing subgenomic DI RNA synthesis from the upstream intergenic region. We discuss possible mechanisms to account for the regulation of this suppression of subgenomic DI RNA synthesis and the ways in which they relate to the general regulation of coronavirus transcription.